CCI and Regulation of Digital Platforms and Blockchain: Will it take a Rule of Reason; Per Se or a Schizophrenic Approach? - Manoj Dalvi; Ahan Gadkari (International Telecommunications Society (ITS), 2022)
India's choice to control its markets was executed in two stages: one for each phase of the country's industrial strategy and philosophy towards resource allocation and market functioning. Between 1950 and 1991, the first phase was defined by a socialist ideology exhibited via a mixed economy and a propensity for government engagement in economic activities. During this time, policymakers were more concerned with avoiding economic power concentration than with stimulating competition. As the Indian economy modernised policymakers moved from preventing concentration of economic power as symbolised by the Monopolies and Restrictive Trade Practices Act (MRTP) of 1969 to the Competition Act 2002 ("Act"), to regulate anti-competitive agreements that have the potential to have a material adverse effect on competition in the Indian economy. In the modern Indian economy, the Competition Commission of India (CCI) has shown inconsistency in its enforcement on platform dominance; this inconsistency may now extend to blockchain as well. The purpose of this paper is to evaluate the necessity of new antitrust tools in the evolving economy of an emergent market and to push for more certainty in the CCI's enforcement of anti-competition laws in India. The increasing digitization of global and Indian markets in recent years, facilitated by the emergence of platforms such as Amazon, Apple, Google, and Facebook have raised questions about the Act's appropriateness and its applications. The CCI has received several complaints over the past few years about creative, technology-driven, two-sided marketplaces that have become a vital element of the Indian economy. In such situations, it becomes easier for certain platforms to practice deep discounting, cash-back offers and other schemes to constantly attract newer users. There is widespread agreement that CCI's reaction to these dynamic markets leaves much to be desired. Since technology has now evolved from the "platform" to "blockchain"; new challenges arise and it has also raised questions if the Act itself needs to be suitably updated to meet the challenges unique to these markets.
Keywords: 330